2018
DOI: 10.1007/s10144-018-0627-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower genetic diversity and hatchability in amphibian populations isolated by urbanization

Abstract: Many amphibian populations worldwide have declined rapidly and been threatened with extinction in the past few decades because of human impacts on the environment. It is well known that urbanization reduces the genetic diversity of isolated populations. The concept that a reduction in genetic diversity leads to lower reproductive fitness has been predominantly supported by studies involving laboratory organisms, but has rarely been tested in wild populations. Here we examined whether genetic diversity affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As a result, small isolated populations will be more subject to deleterious inbreeding effects. It has been reported that R. ornativentris hatchability tends to be low in isolated urban populations (Okamiya & Kusano, 2018;Shiga, 2014). A similar phenomenon of fitness reduction due to the erosion of gene flow and genetic diversity in fragmented habitats has been corroborated for several taxa, ranging from invertebrates to mammals (i.e., Bani et al, 2018;Takahashi et al, 2016;Unfried et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, small isolated populations will be more subject to deleterious inbreeding effects. It has been reported that R. ornativentris hatchability tends to be low in isolated urban populations (Okamiya & Kusano, 2018;Shiga, 2014). A similar phenomenon of fitness reduction due to the erosion of gene flow and genetic diversity in fragmented habitats has been corroborated for several taxa, ranging from invertebrates to mammals (i.e., Bani et al, 2018;Takahashi et al, 2016;Unfried et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our sites had lower heterozygosity than the least genetically diverse population in their study and thus are likely to show severe fitness consequences as a result. Low genetic diversity has also been linked to reduced hatching success in two other pond breeding amphibians (Hynobius tokyoensis and Rana ornativentris) when sites became isolated (Okamiya & Kusano, 2018). However, low genetic diversity at neutral loci is not an indicator of low diversity at loci under selection, which are key to functionality in relation fitness (Beebee, 2018;Mable, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…[61] Hynobius tokyoensis Rana ornativentris Genetic diversity and egg survival were positively affected by the forested area. [33] Bombina variegata Bd prevalence and Bd intensity were highest in two inbred, isolated populations.…”
Section: Hyla Arboreamentioning
confidence: 92%
“…From all studies included in this review (Table S1), thirteen found negative effects of isolation on different demographic fitness proxies (Table 3). Egg and tadpole survival was reduced in small or isolated populations in four European (B. calamita, Rowe and Beebee 2003; H. arborea [54]; R. latastei [55]; and R. temporaria [37]) one North American (Lithobates sevosus [61] and two Japanese species (Hynobius tokyoensis and Rana ornatriventris [33]). With respect to Bd infection the results are more divergent: One study on yellow-bellied toads (B. variegata) found that Bd prevalence and intensity was highest in two isolated and inbred populations [65], while in Litoria verrauxii from Australia Bd infection was absent in an isolated population [46].…”
Section: Effects Of Genetic Diversity On Demographic and Health-relat...mentioning
confidence: 99%
See 1 more Smart Citation